Product Design and Distribution : Emerging Regulatory Approaches for Retail Banking Products - World Bank Group (World Bank, Washington, DC, 2019)
This note discusses emerging international approaches for regulating design and distribution of retail banking products. Such products include deposit, credit, and payment products, being the products that new financial consumers typically acquire first. Policy makers are finding that financial consumer protection measures implemented to date, such as disclosure requirements, while still important, are insufficient to protect consumers against all key risks. Anticipating new or changing risks to consumers has also become more difficult for regulators given rapid financial sector innovation. Regulation of providers’ product design and distribution processes aims to ensure that products distributed in a market are designed to meet the needs of consumers in that market. This discussion note analyses relevant frameworks in a number of jurisdictions and highlights emerging common approaches, including in relation to requirements for governance arrangements, target market assessments, distribution arrangements and product reviews.